2001
DOI: 10.1097/00001648-200103000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption in Relation to 20-Year COPD Mortality and Pulmonary Function in Middle-Aged Men from Three European Countries

Abstract: Alcohol consumption shows a U-shaped relation with all-cause and cardiovascular mortality. To determine whether a similar relation exists between alcohol and chronic obstructive pulmonary disease mortality, we analyzed data on alcohol consumption in 1970 and 20-year mortality from chronic obstructive pulmonary disease among 2,953 middle-aged men from Finland, Italy, and the Netherlands. We also studied alcohol consumption in relation to pulmonary function (FEV1 or FEV0.75) at baseline. We used regression model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
1
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 22 publications
7
64
1
2
Order By: Relevance
“…Alcohol has been identified as an independent predictor of peripheral edema in patients with COPD [38], but was not found to be an independent marker of COPD-related hospitalization [39]. Furthermore, alcohol use has been identified as a significant predictor of COPD mortality [40]. However, a prospective study in a veterans' outpatient population based on subjective assessment of drinking habit found no increased risk of COPD exacerbation independent of tobacco use [41].…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol has been identified as an independent predictor of peripheral edema in patients with COPD [38], but was not found to be an independent marker of COPD-related hospitalization [39]. Furthermore, alcohol use has been identified as a significant predictor of COPD mortality [40]. However, a prospective study in a veterans' outpatient population based on subjective assessment of drinking habit found no increased risk of COPD exacerbation independent of tobacco use [41].…”
Section: Discussionmentioning
confidence: 99%
“…41 Among middle-aged men with COPD, a 20-year study in three European countries found more than double the risk of death among heavy drinkers compared with light to moderate drinkers. 42 Moreover, drinking has been found to negatively impact smoking cessation, 43 a critical recommendation in the management of COPD. 44 Finally, research on Alzheimer's disease and alcohol consumption has been suggestive of brain protection at lower levels of alcohol consumption but cognitive decline at higher levels.…”
Section: Discussionmentioning
confidence: 99%
“…Because alcohol consumption shows a U-shaped curve with cardiovascular mortality (Murray et al, 2002;Rimm et al, 1991), these investigators hypothesized a similar relation between alcohol consumption and COPD mortality. The first study compared twenty-year COPD mortality and pulmonary function to alcohol consumption in three European countries (Tabak et al, 2001b). Analysis of data from 2,953 middle aged men from Finland, Italy and the Netherlands showed reduced COPD mortality in mild drinkers compared to non-drinkers (relative risk of 0.60).…”
Section: Clinical Studies Of Alcohol and Copdmentioning
confidence: 99%